A single-blind randomized trial on the efficacy of telerehabilitation in post-stroke cognitive impairment. CIPS-TER study: rationale, design and methodology - Barucci, Eleonora; Cavaliere, Arianna; Pavan, Eleonora; Formelli, Benedetta; Cecchi, Francesca; Polito, Cristina; Salti, Giulia; Fratini, Filippo; Parenti, Costanza; Pescini, Francesca; Redi, Giacomo; Baldereschi, Marzia; et al. (Frontiers in Stroke, 2025)
Background and aimsCognitive impairment (CI) after stroke is still a neglected consequence compared to other neurological deficits for which rehabilitation pathways are routinely available. Cognitive teleRehabilitation (CTR) represents an emerging approach that has the potential to reduce healthcare costs and potentially reaching many patients. By means of a randomized controlled trial, the aims are to investigate the prevalence of cognitive impairment after stroke and the efficacy of a CTR program in: (a) reducing the risk of CI 6 months after stroke; (b) generalizability of the cognitive training to real life; (c) impact on cognitive performances. In the treated group, feasibility, adherence and appreciation of the CTR will also be evaluated.Methods and outcomesThe CIPS-TER study is a 2-year prospective, single-blind, randomized clinical trial. One hundred patients with ischemic or hemorrhagic stroke will be enrolled in the study, within 5–21 days after onset, and randomized to treatment or standard care. The CTR program will consist of up to 40 h (8 weeks) of individual treatment based on memory, attention, executive functions, and visuospatial tasks to be autonomously performed with a tablet. The study outcomes will be evaluated at 6-month follow-up visit and will include the diagnosis of cognitive impairment, activities of daily living, quality of life, changes in frailty status and cognitive efficiency.ConclusionsCIPS-TER study will expand our knowledge on the potential effect of cognitive rehabilitation on future cognitive and functional decline after stroke.